PEDAGOGICAL METHOD OF ÉTIENNEOZI: NOUVELLE MÉTHODE DE BASSON - Sabriye ÖZKAN (Fırat University, 2019)
In this study, ‘Nouvelle Méthode de Basson’ (New Method for Bassoon) by Étienne Ozi, one of the important French bassoonists and composers of the 18th Century, is examined. This method, which is one of the basic works of bassoon repertoire, is the expanded version of ‘Méthode Nouvelle Etraisonnée pour le Basson,’ also written by Ozi and published in 1787. This new publication includes four additional chapters, as well as more detailed and exemplified theoretical applications. Ozi’s knowledge on difficulties of bassoon technique is reflected in his methods. It is observed that especially his studies and technical exercises, which are focused on specific registers to be developed, facilitate overcoming technical difficulties. Besides writing pedagogical repertoire, the composer made substantial improvements to the mechanical structure of the bassoon. He also did examinations on reed making, which is one of the most important elements for bassoonists. In this study, it is aimed to contribute basson pedagogy by transmitting the innovations brought by Étienne Ozi and his method ‘Nouvelle Méthode de Basson,’ which is an importantpart of basson pedagogy, to the modern bassoonists